Analisis Faktor Motivasi Intrinsik dan Motivasi Ekstrinsik Pengaruhnya terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Mediasi - Siti Noor Hidayati; Antonius Ermiyanto (Universitas Proklamasi 45 Yogyakarta, 2017)
Intrinsic motivation is an employee motivating factor for achievement that comes from within the person, while extrinsic motivation is sourced from outside the person. This research has been conducted to survey on 140 employees of PT Taman Wisata Candi Prambanan consisting of 65 permanent employees and 75 contract employees. The results of this research can be concluded that intrinsic and extrinsic motivation have significant effects to employee performance indirectly with job satisfactions mediation. The influence of extrinsic motivation on job satisfaction and subsequently to employee performance is more dominant than intrinsic motivation. The level of intrinsic motivation, extrinsic motivation, job satisfaction, and employee performance of permanent employees, higher than contract employees, and the difference of them is significant.